Correlation between conjunctival scraping cytology and other clinical dry eye metrics in determination of dry eye related inflammation - Dačić Krnjaja, Bojana M; Potić, Jelena; Raonić, Danijela; Stojković, Milenko (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. New and improved definition of dry eye disease (DED) emphasized that hiperosmolarity and inflammation with initial tear film instability play etiological role. The aim of this study was to explore relation of some commonly used clinical tests to dry eye disease (DED) related inflammation measured by conjunctival scraping cytology. Methods. We examined 100 subjects, 80 of them having DED. We performed Schirmer without anesthesia (Schirmer I), Fluorescein Tear Break Up Time (FTBUT), Rose Bengal (RB), Lid Parallel Conjunctival Folds (LIPCOF), Tear Meniscus Height (TMH) and Tear Ferning (TF) and compared the values to scraping scores of tarsal conjunctiva. Results. FTBUT had the best sensitivity (93.6%). The highest specificity was found with RB (93.2%), but it was also high with Schirmer I, TF and FTBUT (respectively 89.8%, 84.5%, 78.0%). RB and FTBUT had the highest correlation with conjunctival scraping score (r = 0.707, p
Keywords: dry eye syndromes; conjunctiva; cytological techniques; sensitivity and specificity; diagnostic tests, routine; diagnosis, differential